A Cu4I4 Cluster Supported on a Metal‐Dithiolato Complex Anion Causes its Conformational Change Leading to a Doubly‐Bridged Curved Coordination Polymer and its Reactivity with a Diamine Resulting in the Emergence of a [M(diamine)(dithiolate)] System. Issue 26 (16th August 2016) - Madhu, Vedichi; Bolligarla, Ramababu; Naik, Indravath K.; Mekala, Raju; Das, Samar K.
Abstract : When dithiolene‐based coordination complexes [Bu4 N]2 [M II (tdas)2 ] (tdas 2– = 1, 2, 5‐thiadiazole‐3, 4‐dithiolate; M = Ni, Pd, Pt) are reacted separately with CuI, it results in the formation of chain‐like coordination polymers [Bu4 N]2 n [M II (tdas)2 Cu4 I4 ] n [M = Ni (compound1 ), Pd (compound2 ), Pt (compound3 )] in which each metal(bis)dithiolato complex unit supports a Cu I 4 I4 cluster unit. Two of the crystal structures and powder X‐ray diffraction studies confirm that compounds1, 2 and3 are isomorphous with each other showing the abundance of a doubly‐bridged "curved" chain‐like structure formed by the coordination of two "N" donor atoms of each [M II (tdas)2 ] 2– complex unit to two Cu + ions of two adjacent Cu I 4 I4 cluster units and by the coordination of two Cu + ions of a Cu I 4 I4 cluster with its neighbouring two [M II (tdas)2 ] 2– complex anions through their "N" donor atoms from opposite sides. Since the [M II (tdas)2 ] 2– complex anion generally has a planar geometry, which becomes bent upon supporting a Cu I 4 I4 cluster in the present study, the Cu–S interaction in [M II (tdas)2 Cu4 I4 ] 2– is responsible for the bending conformation of the metal–dithiolato complex unit. This bending structure of the complex anion [M II (tdas)2 ] 2– in [M II (tdas)2 Cu4 I4 ] 2– describes a situation where the central part of the complex anion is pulled away towards the Cu I 4 I4 cluster through Cu–S bonds. This causes a "curve‐like" structure throughout the resulting doubly‐bridged chain in compounds1, 2 and3 . The second important aspect of the present work is an interesting reactivity of this doubly‐bridged coordination polymer with a bidentate chelating ligand, tetramethylethylenediamine (TMEDA). Compound [Bu4 N]2 n [Ni II (tdas)2 Cu4 I4 ] n (1 ), a representative member of the series of compounds1 –3, was treated with TMEDA, which resulted in a square planar complex [Ni(tdas)(TMEDA)] (4 ) belonging to a mononuclear [M II (N2 S2 )]‐type system (where N2 = bidentate N∩N donor ligand, mostly a bipyridine type, and S2 = dithiolato ligand) representing an important class of compounds for photophysical properties. Compound4 exhibits emission at room temperature in the visible region. Abstract : A dithiolene‐based coordination complex, on treatment with CuI, results in the formation of a coordination polymer in which each metal(bis)dithiolene complex unit, undergoing a conformational change, supports a Cu I 4 I4 cluster unit.